2013
DOI: 10.3390/ijerph10030747
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Socio-Economic Status on Self-Rated Health: Study of 29 Countries Using European Social Surveys (2002–2008)

Abstract: Studies show that the association between socio-economic status (SES) and self-rated health (SRH) varies in different countries, however there are not many country-comparisons that examine this relationship over time. The objective of the present study is to determine the effect of three SES measures on SRH in 29 countries according to findings in European Social Surveys (2002–2008), in order to study how socio-economic inequalities can vary our subjective state of health. In line with previous studies, income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
53
0
12

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 27 publications
9
53
0
12
Order By: Relevance
“…A Considerando os resultados do modelo final ajustado, verificou-se que, em relação às variá-veis sociodemográficas, diferentemente dos resultados de estudos nacionais 24,25 e internacionais 26,27 , esse estudo não encontrou diferenças na percepção de saúde com o aumento da idade, escolaridade ou sexo. No entanto, nível socioeconômico mais elevado mostrou-se positivamente associado à melhor autoavaliação de saúde, corroborando com a literatura disponível 25,27,28 , inclusive com pesquisa envolvendo esse mesmo grupo de trabalhadores 22 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A Considerando os resultados do modelo final ajustado, verificou-se que, em relação às variá-veis sociodemográficas, diferentemente dos resultados de estudos nacionais 24,25 e internacionais 26,27 , esse estudo não encontrou diferenças na percepção de saúde com o aumento da idade, escolaridade ou sexo. No entanto, nível socioeconômico mais elevado mostrou-se positivamente associado à melhor autoavaliação de saúde, corroborando com a literatura disponível 25,27,28 , inclusive com pesquisa envolvendo esse mesmo grupo de trabalhadores 22 .…”
Section: Resultsunclassified
“…No entanto, nível socioeconômico mais elevado mostrou-se positivamente associado à melhor autoavaliação de saúde, corroborando com a literatura disponível 25,27,28 , inclusive com pesquisa envolvendo esse mesmo grupo de trabalhadores 22 .…”
Section: Resultsunclassified
“…Due to previous observations of social gradients in the psychosocial work environment and in self-rated health (Alvarez-Galvez et al 2013; Hoven and Siegrist 2013), an additional aim was to evaluate the association between work-related stress measures and self-rated health, separately in different SES strata.…”
Section: Introductionmentioning
confidence: 99%
“…". Responses were arranged across the five-item Likert scale: (1) very poor, (2) poor, (3) fair, (4) good and (5) excellent [28]. We binarised the outcome, where responses "very poor"…”
Section: Lifestyle Factorsmentioning
confidence: 99%
“…For instance, a few studies have reported, that adults with higher monthly income were more likely to be overweight/obese [1,4]. Moreover, one recent study showed that relatively high educational attainment was associated with lower risk of mortality and cardiovascular diseases [2]. Also, low income was associated with mental disorders in general population [5].…”
Section: Introductionmentioning
confidence: 99%